Colorative Challenges in English Economic Terminology - Rosyanova, Tatiana S. (Research in Language, 2020)
The paper focuses on multicompound English economic terms with colorative components that constitute a large lexis group, creating constant challenges for translators of economic literature. The introductory part briefly outlines the cognitive aspects of terminology research and discusses advantages of descriptive approach toward economic terminology. Then, it is demonstrated that terminology displays emotive and expressive content by means of connotations as well as such tools as colour-related metaphors. The general trend within this terminological group is the diversity of metaphorical associations that influenced term-formation and the diversity of translating keys that can give the right semantic insight to the translator. Finally, colorative term compounds in economic terminology are regarded as a challenge posed in the context of translation.